# Inequality

$$a,b,c$$ are positive real numbers and $$abc=1$$. Prove that

$$\frac{1}{2+a} + \frac{1}{2+b} + \frac{1}{2+c} \geq \frac{1}{1+a+b} + \frac{1}{1+b+c} + \frac{1}{1+c+a}$$

Note by Fahim Shahriar Shakkhor
3 years, 11 months ago

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold
- bulleted- list
• bulleted
• list
1. numbered2. list
1. numbered
2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in $$...$$ or $...$ to ensure proper formatting.
2 \times 3 $$2 \times 3$$
2^{34} $$2^{34}$$
a_{i-1} $$a_{i-1}$$
\frac{2}{3} $$\frac{2}{3}$$
\sqrt{2} $$\sqrt{2}$$
\sum_{i=1}^3 $$\sum_{i=1}^3$$
\sin \theta $$\sin \theta$$
\boxed{123} $$\boxed{123}$$

Sort by:

$$\dfrac{1}{2+a}+\dfrac{1}{2+b}+\dfrac{1}{2+c} \geq \dfrac{1}{1+a+b}+\dfrac{1}{1+b+c}+\dfrac{1}{1+c+a} \\ \Rightarrow \dfrac{(2+a)(2+b)+(2+b)(2+c)+(2+a)(2+c)}{(2+a)(2+b)(2+c)} \geq \dfrac{(1+a+b)(1+b+c)+(1+a+b)(1+a+c)+(1+a+c)(1+b+c)}{(1+a+b)(1+a+c)(1+b+c)} \\ \Rightarrow \dfrac{ (4+2a+2b+ab)+(4+2b+2c+bc)+(4+2a+2c+ac)}{8+4a+4b+4c+2ab+2ac+2bc+abc} \geq \dfrac{(1+a+2b+c+ab+bc+ac+b^2)+(1+2a+b+c+ab+bc+ac+a^2)+(1+a+b+2c+ab+bc+ac+c^2)}{2(a+b+c)+3(ab+bc+ca)+(a^2+b^2+c^2)+(a+b+c)(ab+bc+ca)} \\ \Rightarrow \dfrac{12+4(a+b+c)+(ab+bc+ca)}{9+4(a+b+c)+2(ab+bc+ca)} \geq \dfrac{3+4(a+b+c)+3(ab+bc+ca)+(a^2+b^2+c^2)}{2(a+b+c)+3(ab+bc+ca)+(a^2+b^2+c^2)+(a+b+c)(ab+bc+ca)}$$

Let $$x=a+b+c$$ and $$y=ab+bc+ca \\ a^2+b^2+c^2=(a+b+c)^2-2(ab+bc+ca)=x^2-2y$$

Putting the values we get,

$$\displaystyle \dfrac{12+4x+y}{9+4x+2y} \geq \dfrac{3+4x+x^2+y}{2x+y+x^2+xy} \\\Rightarrow 3x^2y+xy^2+6xy-5x^2-y^2-24x-3y-27 \geq 0 \\\Rightarrow (\dfrac{5}{3}x^2y-5x^2)+(\dfrac{4}{3}x^2y-12x)+(\dfrac{xy^2}{3}-y^2)+(\dfrac{xy^2}{3}-3x) + (\dfrac{xy^2}{3}-3y) + (3xy-9x) + (3xy-27) \geq 0$$

which is true because $$x,y\geq3$$

- 3 years, 8 months ago